1999
DOI: 10.1017/s1368980099000221
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing different iodine interventions in school children

Abstract: Objective: The purpose of this trial was to compare three different iodine interventions. Design: School children aged 8-10 years were randomized into one of three groups: group A was provided with iodized salt by researchers with an iodine concentration of 25 ppm; group B purchased iodized salt from the market; and group C was similar to group B with the exception that they were given iodized oil capsules containing 400 mg iodine at the beginning of the study. Salt iodine content was measured bimonthly for 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
3
13
0
2
Order By: Relevance
“…A study from Tanzania, where the prevalence of goiter used to be 25 %, showed that within 12 years of initiating USI, 84 % of the population consumes iodized salt, and 94.5 % of 6-12 year old children have normal sized thyroid glands [38]. Similarly, the GR of Chinese schoolchildren affected by mild IDD dropped from 18 to 5-9 % after just 18 months of salt iodization supplement [39]. According to a recent ICCIDD letter [15], African countries such as Burundi, Kenya, Nigeria, Uganda, Tunisia, Namibia, Zimbabwe and Libya have successfully achieved USI, and their coverage of households with iodized salt is more than 90 %.…”
Section: Intervention Strategiesmentioning
confidence: 99%
“…A study from Tanzania, where the prevalence of goiter used to be 25 %, showed that within 12 years of initiating USI, 84 % of the population consumes iodized salt, and 94.5 % of 6-12 year old children have normal sized thyroid glands [38]. Similarly, the GR of Chinese schoolchildren affected by mild IDD dropped from 18 to 5-9 % after just 18 months of salt iodization supplement [39]. According to a recent ICCIDD letter [15], African countries such as Burundi, Kenya, Nigeria, Uganda, Tunisia, Namibia, Zimbabwe and Libya have successfully achieved USI, and their coverage of households with iodized salt is more than 90 %.…”
Section: Intervention Strategiesmentioning
confidence: 99%
“…Thirteen RCTs that assessed iodine intake and UI in children and adolescents were identified. Two papers reported data for boys and girls separately, two studies had two separate iodine intervention dose groups, and two studies had three iodine‐treated dose groups; therefore, 21 estimates were included in the analysis. These 21 estimates included a total of 3,397 participants with an age range of 4 to 16 years (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The median duration of the included studies was 12 weeks (range, 2–192 weeks). In four RCTs, iodine supplements were given in the form of potassium iodide, in doses that ranged from 100 to 1,500 μg/day. Iodized oil supplementation was used in 10 RCTs, with doses ranging from 120 to 960 mg/day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Это увеличение сходно с дан ными ранее проведенных исследований в других странах [19,37,38,41]. В этих исследованиях было обнаружено увеличение в уровня ЙМ пределах от 65 до 115 мкг/л через один год после использования в питании ЙС.…”
Section: исходноеunclassified